Potensi Stok dan Kapasitas Mitigasi CO₂-e Ekosistem Mangrove di Pesisir Teluk Ambon Dalam, Kota Ambon - Sadali IE; Alex S. W. Retraubun; Johannes M. S. Tetelepta; Charlotha I. Tupan; Rahman Rahman (Universitas Pattimura, 2026)
Mangrove ecosystems are important blue carbon reservoirs with high potential for climate change mitigation; however, site-specific assessments in semi-enclosed tropical bays, particularly in eastern Indonesia, remain limited. This study estimates the carbon stock and CO₂-e sequestration potential of mangrove ecosystems in Inner Ambon Bay. Field data were collected from four sites—Passo, Waiheru, Nania, and Negeri Lama—through measurements of stand structure, biomass, and sediment carbon to a depth of 100 cm. Biomass was estimated using species-specific allometric equations, while sediment carbon was analyzed based on bulk density and organic carbon content. The results show substantial spatial variation, with total carbon stocks ranging from 425.0 to 1,205.0 ton C/ha, highest in Passo and lowest in Negeri Lama. Sediment carbon dominated the total stock, contributing more than 75%, indicating the critical role of belowground pools in long-term carbon storage. The CO₂-e sequestration potential ranged from 1,560.1 to 4,418.1 ton CO₂-e/ha, reflecting strong mitigation capacity. This study provides one of the first integrated, site-specific assessments of aboveground, belowground, and sediment carbon stocks in a semi-enclosed tropical bay in eastern Indonesia, linking spatial variability to ecosystem-based CO₂-e mitigation capacity. These findings highlight the strategic importance of mangrove conservation for climate mitigation and support the development of blue carbon-based management and financing mechanisms.